2017
DOI: 10.3382/ps/pex171
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of global organic matrix in normal and pimpled chicken eggshells

Abstract: The organic matrix from normal and pimpled calcified chicken eggshells were dissociated into acid-insoluble, water-insoluble, and facultative-soluble (both acid- and water-soluble) components, to understand the influence of shell matrix on eggshell qualities. A linear correlation was shown among these 3 matrix components in normal eggshells but was not observed in pimpled eggshells. In pimpled eggshells, the percentage contents of all 4 groups of matrix (the total matrix, acid-insoluble matrix, water-insoluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…In the present study, the organic matrix in calcified eggshells were dissociated into acid-insoluble, water-insoluble, and facultative-soluble (both acid and water soluble) components. We had previously reported the significant correlations between both egg weight and calcified eggshell weight and the percentage contents of all 4 groups of matrix (3 matrix components and total matrix) in per gram of shell, and the significant correlations between both calcified eggshell weight and shell thickness and the amounts of all 4 groups of matrix in an individual calcified shell ( Liu et al., 2017 ). However, the present results showed that the constituent ratios of 3 matrix components in the whole matrix, and the percentage contents of 3 matrix components in per gram of shell showed no significant correlations with any geometrical parameters, this meant both the constituent ratios and percentage contents of 3 matrix components showed no significant effects on egg contour.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, the organic matrix in calcified eggshells were dissociated into acid-insoluble, water-insoluble, and facultative-soluble (both acid and water soluble) components. We had previously reported the significant correlations between both egg weight and calcified eggshell weight and the percentage contents of all 4 groups of matrix (3 matrix components and total matrix) in per gram of shell, and the significant correlations between both calcified eggshell weight and shell thickness and the amounts of all 4 groups of matrix in an individual calcified shell ( Liu et al., 2017 ). However, the present results showed that the constituent ratios of 3 matrix components in the whole matrix, and the percentage contents of 3 matrix components in per gram of shell showed no significant correlations with any geometrical parameters, this meant both the constituent ratios and percentage contents of 3 matrix components showed no significant effects on egg contour.…”
Section: Discussionmentioning
confidence: 98%
“…Eggs from 3 breeds, Hy-line Brown Chicken, Shaoxing Duck, and Zhedong White Goose, were used for this analysis. Based on the method ( Liu et al., 2017 ), the organic matrix components were extracted from each calcified eggshell. Briefly, the eggshell was individually powdered using mortar and pestle, then decalcified by stirring with 10% acetic acid at 20°C for about 18 h. The amount of 10% acetic acid used was about 22–25 mL per gram shell powder, and the acetic acid was added stepwise as the proportion of 35:35:30, the first 2 steps of decalcification were individually carried out over 3–4 h, and the last time decalcification was performed overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Pimpled eggs ( PE ), however, are a defect characterized by the presence of extra-calcified granules on either end of the eggshell. PE have weaker shells and are more susceptible to breaking compared to normal eggs ( NE ) under the same conditions ( Liu et al, 2017a , b ). The strength of the eggshell weakens further if the pimples are removed from the surface of PE ( Roland Sr et al, 1975 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, statistics show that egg production in Malaysia has increased dramatically to 773 thousand tonnes, with an expected annual growth rate of 3.6% by 2020. In this case, ES waste can be used as a source of calcium carbonate (CaCO 3 ), which accounts for approximately 95% of a shell mass and 5% of organic materials such as sulfated polysaccharides, collagen, and other proteins [ 3 ]. Furthermore, CaCO 3 has been used to remove manganese, cadmium, lead, zinc, nickel, and chromium [ 4 ]; additionally, CaCO 3 is known for having good morphology and porosity and removing more than 90% of metal ions when the pH, contact time, agitation speed, and adsorbent dosage are optimized.…”
Section: Introductionmentioning
confidence: 99%